Germaniści o dydaktyce literatury = Germanists about the didactics of literature - Ruszczakowa, Hanna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
In the article the opinions of participants of the conference devoted to the didactics of literature published in the work: Literaturunterricht heute - warurn und wie? (Verlag Freiburg im Breisgau 1978) are presented.
Keywords: dydaktyka literatury